(untitled) (Zeszyty Naukowe Wydziału Nauk Ekonomicznych, 2021)
The brand is a component of intangible and legal assets, which is not as yet commonly identified and presented in the balance sheets of economic entities. The problem is, however, lack of tradition and difficulties connected with the valuation of this intangible value. This constitutes a great challenge to managerial accountancy. At presents, methods are applied which are based on the cost, comparative and income approaches, which are connected with methods of valuation of the company’s tangible assets. Brand’s management guarantees large and measurable benefits, which provide values to their owners in the form of increased sales, an increased company’s financial result, and benefits from the possession of a specific image or capital of reputation